2013
DOI: 10.1177/0269881113494939
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal formulation of erythropoietin (EPO) showed potent protective activity against amyloid toxicity in the Aβ25-35 non-transgenic mouse model of Alzheimer’s disease

Abstract: Erythropoietin (EPO) promotes neurogenesis and neuroprotection. We here compared the protection induced by two EPO formulations in a rodent model of Alzheimer's disease (AD): rHu-EPO and a low sialic form, Neuro-EPO. We used the intracerebroventricular administration of aggregated Aβ₂₅₋₃₅ peptide, a non-transgenic AD model. rHu-EPO was tested at 125-500 µg/kg intraperitoneally and Neuro-EPO at 62-250 µg/kg intranasally (IN). Behavioural procedures included spontaneous alternation, passive avoidance, water-maze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 67 publications
2
43
2
Order By: Relevance
“…Since EPO and EPO derivatives are known to have beneficial effects on memory formation [4, 11, 13, 14, 16, 40, 5052], it was evaluated whether Epobis also can improve memory formation in healthy animals. Epobis was found to improve the social recognition of healthy adult rats 3 days, but not 1 h, after treatment (Figure 6), suggesting that Epobis-induced changes in gene transcription and other downstream effects lasting more than 1 h are required for the beneficial effects on memory to appear or that the effects on memory peak several days after Epobis exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since EPO and EPO derivatives are known to have beneficial effects on memory formation [4, 11, 13, 14, 16, 40, 5052], it was evaluated whether Epobis also can improve memory formation in healthy animals. Epobis was found to improve the social recognition of healthy adult rats 3 days, but not 1 h, after treatment (Figure 6), suggesting that Epobis-induced changes in gene transcription and other downstream effects lasting more than 1 h are required for the beneficial effects on memory to appear or that the effects on memory peak several days after Epobis exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EPO has beneficial effects on memory and mood of animals and humans with depression-like symptoms [11]. Animal studies using EPO or EPO derivatives have demonstrated an improved memory and a reduced endothelial and neuronal degeneration in models of Alzheimer's disease [1214], a protection against experimental cerebral malaria and pneumococcal meningitis [15, 16], downregulation of proinflammatory cytokines and upregulation of anti-inflammatory cytokines in a model of amyotrophic lateral sclerosis [17], a reduction of progressive retinal degeneration [18], and neuroprotective effects in relation to status epilepticus [19] and cervical subacute spinal cord compression [20]. Importantly, most of these beneficial effects of EPO are believed to be unrelated to the erythropoietic effects of EPO but not necessarily unrelated to signaling through the EPO receptor [13].…”
Section: Introductionmentioning
confidence: 99%
“…The international PCT filing was done in June 2017 (PCT/CU2017/050005). The effect of Neuro-EPO on nervous cells was also published in Parra and Rodríguez 2012 [17], Maurice et al, 2013 [18] and Rodríguez et al, 2017 [19]. New clinical trials to test the efficacy of the basic rhEPO in other indications are designed and will be conducted, so new patent applications could arise.…”
Section: Patents Around Basic Form Of Epomentioning
confidence: 92%
“…Second, another avenue of investigation for EPO and TBI could involve targeting more specific pathways controlled by EPO such as protein kinase B (Akt) that can foster a number of protective pathways in the nervous system with EPO [112115]. Other pathways that can modulate the protective effects of EPO include mTOR [68,80,82,83], AMPK [41,96], sirtuins [72,116,117], wingless pathways [68,72,91,118,119], and forkhead transcription factors [57,113,120].…”
Section: Erythropoietin and Traumatic Brain Injury: Translating Expermentioning
confidence: 99%